Utilizing Fluorescent Nanoscale Particles to Create a Map of the Electric Double Layer - (:unkn) unknown (My University, 2023)
The interactions between charged particles in solution and an applied electric field follow several models, most notably the Gouy-Chapman-Stern model, for the establishment of an electric double layer along the electrode, but these models make several assumptions of ionic concentrations and an infinite bulk solution. As more scientific progress is made for the finite and single molecule reactions inside microfluidic cells, the limitations of the models become more extreme. Thus, creating an accurate map of the precise response of charged nanoparticles in an electric field becomes increasingly vital. Another compounding factor is Brownian motion’s inverse relationship with size: large easily observable particles have relatively small Brownian movements, while nanoscale particles are simultaneously more difficult to be observed directly and have much larger magnitude Brownian movements. The research presented here tackles both cases simultaneously using fluorescently tagged, negatively charged, 20 nm diameter polystyrene nanoparticles. By utilizing parallel plate electrodes within a specially constructed microfluidic device that limits the z-direction, the nanoparticle movements become restricted to two dimensions. By using one axis to measure purely Brownian motion, while the other axis has both Brownian motion and ballistic movement from the applied electric field, the ballistic component can be disentangled and isolated. Using this terminal velocity to calculate the direct effect of the field on a single nanoparticle, as opposed to the reaction of the bulk solution, several curious phenomena were observed: the trajectory of the nanoparticle suggests that the charge time of the electrode is several magnitudes larger than the theoretical value, lasting for over a minute instead of tens of milliseconds. Additionally, the effective electric field does not reduce to below the Brownian limit, but instead has a continued influence for far longer than the model suggests. Finally, when the electrode was toggled off, a repeatable response was observed where the nanoparticle would immediately alter course in the opposite direction of the previously established field, rebounding with a high degree of force for several seconds after the potential had been cut before settling to a neutral and stochastic Brownian motion. While some initial hypotheses are presented in this dissertation as possible explanations, these findings indicate the need for additional experiments to find the root cause of these unexpected results and observations.
Keywords: Brownian Motion; Electric Double Layer; Fluorescence Microscopy; Microfluidics; Nanoparticles